El jurgo cooperativo para el desarrollo de la creatividad de los niños de inicial 2 del centro de educación inicial "Dolores Veintimilla de Galindo" de ciudad Riobamba, provincia de Chimborazo - Zavala Pulla, Daniela Nataly (2024)
The research, centered on the development of creativity in children in Pre-school II through cooperative play, is presented as a valuable contribution to the educational field with a specific focus on the "Dolores Veintimilla de Galindo" Early Education Center in the city of Riobamba, Province of Chimborazo. The choice of cooperative play as the object of study suggests an interest in exploring dynamics that encourage collaboration and teamwork among children in the initial stage of their education. This choice is crucial, as it recognizes the importance of not only developing individual skills, but also promoting social and emotional skills from an early age. Creativity is established as the central core of the development that is sought to be enhanced. Given the growing relevance of creativity in contemporary society, understanding how cooperative play can influence this specific aspect is essential. It is hoped that the results and conclusions of the research will shed light on the effectiveness of these ludic practices in stimulating children's creativity. The findings will not only benefit the educational community of the Centro de Educación Inicial "Dolores Veintimilla de Galindo", but can also be extrapolated and applied in other similar contexts. Educators, parents and professionals interested in the integral development of children will find valuable information that could improve pedagogical strategies and support for creativity in early childhood. The research will ultimately contribute to the accumulated knowledge on the relationship between cooperative play and creative development in early education.